The basic practice of statistics - Moore, David S. (W.H. Freeman and Co, 2007)
This book offers a number of innovations, including briefer chapters, a new problem-solving process, a wealth of new exercises, and new all-in-one place StatsPortal, with all the electronic tools instructors and students need